Vibration Control of Quarter Car Model Using Modified PID Controller - Matrood, Mustafa Mohammed; Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2021)
The purpose of this research is to control a quarter car suspension system and also to reduce the fluctuated movement caused by passing the vehicle over road bump using modified PID (Proportional Integral and Derivative) controller. The proposed controller deals with dual loop feedback signals instead of single feedback signal as in the conventional PID controller. The structure of the modified PID controller was created by moving the proportional and derivative actions in the feedback path while remaining the integral action in the forward path. Thus, high accuracy results were obtained. Firstly, modelling and simulation of linear passive suspension system for a quarter car system was performed using Matlab – Simulink software. Then the linear suspension system was activated and simulated by using an active hydraulic actuator to generate the necessary force which can be regulated and controlled by the proposed controller. The performance of whole system has been enhanced with a modified PID controller.